Myliobatis goodei, southern eagle ray - Carlson, J. (2020)
The Southern Eagle Ray (Myliobatis goodei) is a medium-sized (to at least 115 cm DW) coastal eagle ray that occurs in the Western Central and Southwest Atlantic Oceans from South Carolina and Florida, USA and Quintana Roo, Mexico to San Jorge Gulf, Santa Cruz, Argentina. It inhabits continental shelves from inshore to depths of 181 m. It is captured using artisanal longlines, gillnets, beach seines, and in industrial shrimp trawls. This species is inferred to be stable or increasing in the Western Central Atlantic, based on its similarity to the Bullnose Eagle Ray (Myliobatis freminvillei). In the Southwest Atlantic artisanal fisheries are intense, further there are largely unmanaged commercial trawl and longline fisheries in many areas. In Brazil, landings of eagle rays have been reduced by 60% over 2000?2012 in Santa Catarina State, and a reduction of 91% in Rio Grande do Sul since the 1980s. This inshore eagle ray has no refuge at depth and is exposed to intense and often unmanaged fishing pressure throughout the Atlantic South American portion of its range and there it is suspected that this species has undergone a population reduction of >80% over the past three generation lengths (44 years), but is stable in the Western Central Atlantic. Overall, based its range with the almost all threats found in the Southwest Atlantic, the suspected low productivity of the species, this species is suspected to have undergone a population reduction of 30 49% in three generation lengths (44 years) due to levels of exploitation, and it is assessed as Vulnerable A2d.